2021
DOI: 10.1111/jcmm.16910
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl oligopeptidase inhibition reduces alpha‐synuclein aggregation in a cellular model of multiple system atrophy

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…The results of recent research are consistent with the above possibilities: the addition of human preformed SYN fibrils to mouse OLGs triggered an increase in endogenous SYN, which was critical for its aggregation with TPPP [14]; in agreement with this, in rat OLN-AS7 and human MO3.13 OLG models of MSA, TPPP transfection significantly increased the levels of both SYN mRNA and SYN protein [42]. Moreover, SYN fibrils interfered with the production of proteins associated with neuromodulation and myelination [43].…”
Section: Pathological Interaction Between Tppp and Synsupporting
confidence: 79%
“…The results of recent research are consistent with the above possibilities: the addition of human preformed SYN fibrils to mouse OLGs triggered an increase in endogenous SYN, which was critical for its aggregation with TPPP [14]; in agreement with this, in rat OLN-AS7 and human MO3.13 OLG models of MSA, TPPP transfection significantly increased the levels of both SYN mRNA and SYN protein [42]. Moreover, SYN fibrils interfered with the production of proteins associated with neuromodulation and myelination [43].…”
Section: Pathological Interaction Between Tppp and Synsupporting
confidence: 79%
“…PEO is implicated in neurodegeneration and neuroinflammation, and is considered a drug target for the enhancement of memory in dementia [ 182 ]. Inhibition of PEO reduces α-synuclein aggregation in PD [ 183 ]. increases α-synuclein degradation by neural cells [ 184 ].…”
Section: Traditional Chinese Medicinal Formulations Used To Treat Alz...mentioning
confidence: 99%
“…Various studies demonstrated that the physiological role of POP is to regulate PP2A; particularly, POP inhibition was recently shown to increase PP2A activity, thereby reducing oxidative stress [ 39 , 40 ]. Moreover, PP2A serves an important role in protection against renal inflammation [ 41 ].…”
Section: Resultsmentioning
confidence: 99%